1999
DOI: 10.1177/001440299906500409
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the IDEA Transition Mandates

Abstract: A policy study initiated in 1996 investigated implementation of the transition mandates of the Individuals with Disabilities Education Act (IDEA) in nine sites across the United States. Five sites were identified as model sites because they had a national reputation for effective implementation of transition policies and practices, while four were identified as representative sites demonstrating progress in the face of challenges typically associated with local level implementation. Visits to each site include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 17 publications
(16 reference statements)
3
52
0
Order By: Relevance
“…However, implementation of these transition reform efforts has been slow, with most states failing to achieve even minimal levels of compliance (Grigal, Test, Beattie, & Wood, 1997;Hasazi, Furney, & DeStefano, 1999). The National Council on Disability (2000) reported that "88% or 44 states failed to ensure compliance with transition requirements" (p. 89).…”
Section: Spring 2004mentioning
confidence: 99%
“…However, implementation of these transition reform efforts has been slow, with most states failing to achieve even minimal levels of compliance (Grigal, Test, Beattie, & Wood, 1997;Hasazi, Furney, & DeStefano, 1999). The National Council on Disability (2000) reported that "88% or 44 states failed to ensure compliance with transition requirements" (p. 89).…”
Section: Spring 2004mentioning
confidence: 99%
“…The lack of a unified transition process between high school and post-school employment is part of the problem. Once youth with disabilities exit high school, they are typically referred to adult service agencies that have not collaborated with special education programs to design a "seamless" transition for these young adults (Certo, et al, 2003;Hasazi, Furney, & DeStefano, 1999). Other barriers to successful post-school planning include not having the opportunity to discuss post-school plans with professionals, not being involved in the Individualized Education Plan (IEP) process, and not receiving career development services that assist in transition (Hitchings, et al, 2001;Hitchings, Retish, & Horvath, 2005;Janiga & Costenbader, 2002).…”
Section: Among Many Others)mentioning
confidence: 99%
“…Moreover, as a group, youth with disabilities, when compared to their peers without disabilities, are characterized by a gap in school completion, post-school employment, and entry to higher education institutions (Hasazi, Furney, & DeStefano, 1999; National Center on Secondary Education and Transition [NCSET], 2000). These discrepancies are even more pronounced for court-involved youth (or juveniles) with disabilities (Bullis, Yovanoff, Mueller, & Havel, 2002).…”
Section: Educational Failure As a Pathway To Juvenile Delinquencymentioning
confidence: 99%